Emerging Thin‐Film Photovoltaic Technologies. Issue 4 (April 2015) - Hermes, Wilfried; Waldmann, Daniel; Agari, Michaela; Schierle‐Arndt, Kerstin; Erk, Peter; Machhammer, Otto
Abstract With free fuel from the sun, the cost of photovoltaic (PV) power is just related to conversion efficiency, lifetime and cost of the PV system. After successful optimization, crystalline silicon took the lead and a respectable PV market developed under the umbrella of subsidies. Thin‐film PV technologies provide the opportunity to reduce PV costs radically. They need less active material and their production processes are lean. In addition, flexibility, low weight and transparency will open new markets. This review gives an overview about the status of three emerging thin‐film technologies.